Claude de Seyssel and Society Concept of George Gemistus Plethon - E. V. Kuleshova; D. N. Starostin (Научный диалог)
The article deals with the ideas of Claude de Seyssel (1450—1520). Attention is paid to the fact that these ideas were based on an analysis, based on the model proposed by Plato, of the oligarchic form of government as a real form of existence of the republic in contemporary Venice and a study of the applicability of this model to France. The relevance of the work is due to the appearance of a number of works in which one can see that the views of Claude de Seyssel were similar not only to the views of the Italian humanists, but also to the utopian ideas of the reorganization of Byzantium by George Gemistus Plethon (1355/1360—1452/1454). The authors of the article argue that the ideas of Claude de Seyssel should be considered in a broader context than was previously accepted in historical science. It is shown in the article that it was Claude de Seyssel who drew attention to the importance of the military class and its rights as the most important principle for the formation of European monarchies in the context of problems common to Italian and Byzantine humanists. It is proved that he became a kind of transmission link between Italian and Byzantine humanism, on the one hand, and French humanism, on the other, and significantly influenced the development of socio-political and historical concepts of French thinkers of the 16th-17th centuries.